Sodium Nitroprussid and Adenosine-Activated Potassium Channel in Aortic Smooth Muscle Isolated From Female Rats - Al-Habib, Omar A.M.; Muhammmad, Chinar M. (Science Journal of University of Zakho, 2014)
Sodium Nitroprusside (SNP) and Adenosine (Ado) are potent drugs used in the treatment of cardiovascular diseases. Nitric oxid (NO) is produced from virtually all cell types composing the cardiovascular and regulates vascular function through fine regulation of excitation–contraction coupling. Adinosine endogenous metabolites play a major role in coronary autoregulation. Therefore, the aim of the present study was to investigate the contribution of NO and Ado mediated relaxation in rat aortic smooth muscle in intact and denuded endothelium rings precontracted with phenylepherine (PE). The thoracic aorta was isolated, cut into rings, and mounted in organ-bath chambers and isometric tension was recorded using powerLab Data Acquisition System (Model ML 870). According to the results of the current study, incubation of aortic rings with Glybenclamide (GLIB) decreased the relaxation response induced by Ado (the vasodilation value rate decrease from 41.07±6.7 control to 18.54±4.6) in intact aortic rings. L-nitroarginine methylester (L-NAME), not abolished the response induced by SNP, whereas Nifedipine significantly enhanced the response induced by SNP in a dose-dependent manner in intact endothelium rings. The relaxation to Ado in intact aortic rings was slightly decreased (6.88± 1.01), but not abolished completely after incubation with Caffeine (Ado receptors antagonist). On the other hand, removing endothelium did not attenuated the vasorelaxation induced by SNP and increased relaxation response. While, vasorelaxation of Ado in aortic rings were partially attenuated by removing endothelium. These results suggested that (1) ATP-dependent potassium channel (KATP) did not involve in SNP inducing vasorelaxation, while have a role in Ado mediated vasorelation. (2) Vasorelaxation effect of NO is endothelium independent, while, Ado relaxation effect is endothelium dependent.